Viral ion channels: structure and function. - Fischer, W; Sansom, MS (2002)
Viral ion channels are short auxiliary membrane proteins with a length of ca. 100 amino acids. They are found in enveloped viruses from influenza A, influenza B and influenza C (Orthomyxoviridae), and the human immunodeficiency virus type 1 (HIV-1, Retroviridae). The channels are called M2 (influenza A), NB (influenza B), CM2 (influenza C) and Vpu (HIV-1). Recently, in Paramecium bursaria chlorella virus (PBCV-1, Phycodnaviridae), a K+ selective ion channel has been discovered. The viral channels form homo oligomers to allow an ion flux and represent miniaturised systems. Proton conductivity of M2 is established; NB, Vpu and the potassium channel from PBC-1 conduct ions; for CM2 ion conductivity is still under proof. This review summarises the current knowledge of these short viral membrane proteins. Their discovery is outlined and experimental evidence for their structure and function is discussed. Studies using computational methods are presented as well as investigations of drug-protein interactions.